Associations of anxiety and depression with restless leg syndrome: a systematic review and meta-analysis - An, Tianyang; Sun, Haiyang; Yuan, Lu; Wu, Xiuling; Lu, Baoquan (Frontiers in Neurology, 2024)
The levels of anxiety and depression among patients with restless leg syndrome (RLS) are controversial. The aim of this systematic review and meta-analysis was to compare the levels of depression and anxiety among individuals with RLS with those of healthy controls.We conducted an extensive electronic search of the PubMed, Web of Science, EMBASE, and Cochrane Library databases from their inception dates to June 20, 2023. Studies presenting data on depression and anxiety in individuals with RLS were included, and a comprehensive meta-analysis was performed.Results: Twenty-one studies matched the inclusion criteria. Significantly more depressive symptoms were present in the individuals with RLS than in those without RLS, as measured by the Beck Depression Inventory [mean difference (MD) = 6.58, 95% confidence interval (CI) = 5.54-7.62, p < 0.01; heterogeneity I 2 = 0%, p = 0.99)]. Similarly, the results from the Beck Anxiety Inventory indicated that there were significantly more pronounced anxiety symptoms in the individuals with RLS than in those without RLS (MD = 9.30, 95%CI = 7.65-10.94, p < 0.01; heterogeneity I 2 = 0%, p = 0.92). The other anxiety and depression scales also yielded statistically significant results. Significant heterogeneity was observed in the Hamilton Depression Rating Scale and Hamilton Anxiety Rating Scale, with the primary contributing factor probably being the scoring criteria of the scales.This meta-analysis found that the levels of depression and anxiety symptoms were significantly higher in individuals with RLS than in their healthy counterparts.